Jejak Transformasi Budaya: Evolusi Komunikasi Manusia dari Era Lisan hingga Algoritma Digital - Rangga Saptya Mohamad Permana; Elis Suryani Nani Sumarlina; Undang Ahmad Darsa; Abdul Rasyad (Universitas Hamzanwadi, 2026)
Since the beginning of civilization, communication has progressed from simple gestures and body language to intricate digital systems. Communication is not merely a means of transmitting information; it is also an essential social process in the production of meaning, cultural identity, and societal evolution. This research seeks to examine the evolution of communication as a driving force in the formation, preservation, and transformation of culture over time. Using a descriptive qualitative method and an in-depth literature review approach, this study integrates perspectives from history, anthropology, sociology, and digital media studies, enriched with archaeological data and analysis of two contemporary regulatory case studies: GDPR in the European Union and misinformation handling in the United States. The findings show that every breakthrough in communication—writing, printing, and digitalization—causes structural changes in society, such as the emergence of imagined communities, the differentiation of intellectual classes, and the formation of a surveillance capitalism culture. In the digital era, this shift accelerates cultural norm changes and fosters the emergence of new symbols in cross-cultural communication, while also posing severe issues such as social fragmentation, access inequality, and a digital ethics crisis. This study underlines the importance of a balanced regulatory strategy, collective ethical awareness, and cross-disciplinary cooperation in managing the effects of communication evolution.